Parasites and Public Health: Global Challenges and Emerging Insights - Dr. V. Basil Hans (International Journal of Tropical Medicines, 2025)
Parasitic illnesses are still a big problem for health around the world, especially in developing nations where sanitation and access to healthcare are restricted. Protozoa, helminths, and ectoparasites are all types of parasites that can damage many organ systems and cause both short-term and long-term health problems. This article looks at how parasites affect human health in different ways, focussing on common infections including malaria, schistosomiasis, and toxoplasmosis. Parasitic infections can cause a wide range of problems, including starvation, anaemia, neurological problems, and a weakened immune system. Also, the way parasites interact with the host's immune system can make co-infections worse and affect how well immunisations work. We also talk about new findings on how parasites may cause autoimmune illnesses and how they might be used in immunotherapy. To make focused public health interventions, better diagnostic tools, and better treatment strategies, we need to know all the consequences of parasites.
Keywords: and the immune system effects on Global Health; human health; parasites; protozoa and helminths